481 Solriamfetol Titration & AdministRaTion (START): Characteristics of patients with narcolepsy and solriamfetol prescriber rationale. (3rd May 2021) - Thorpy, Michael; Hyman, Danielle; Parks, Gregory; Chen, Abby; Foley, Catherine; Ito, Diane; Singh, Haramandeep
Abstract: Introduction: Pharmacotherapy for excessive daytime sleepiness (EDS) associated with narcolepsy is diverse, with factors such as efficacy, side effects, and tolerance influencing treatment decisions. Solriamfetol (Sunosi®), a dopamine/norepinephrine reuptake inhibitor, is approved (US and EU) to treat EDS in adults with narcolepsy (75–150 mg/day) or obstructive sleep apnea (OSA) (37.5–150 mg/day). This study characterized real-world patients with narcolepsy starting solriamfetol and prescribers' rationales for initiating treatment. Methods: This virtual, descriptive study included a quantitative retrospective patient chart review among US-based physicians prescribing solriamfetol. Target enrollment was 25 physicians treating patients with EDS associated with OSA or narcolepsy. Treatment initiation was classified as de novo (no EDS medication prior to solriamfetol), transition (switched/switching from existing EDS medications onto solriamfetol), or add-on (adding solriamfetol to current EDS medication). Results: Twenty-six physicians participated. Seventy patients with narcolepsy were analyzed (type 1, n=24; type 2, n=46; mean±SD age, 40±11 years; 57% female; 6 also had OSA); EDS was primarily moderate (59%) or severe (36%). Twenty-two patients (31%) were obese (BMI≥30); other common physician-reported comorbidities were migraine headaches (n=12, 17%), depression (n=10, 14%), and cardiovascular disorders (n=10, 14%). Solriamfetol initiation was de novo for 19 (27%) patients, transition for 31 (44%), and add-on for 20 (29%). Patients transitioning to solriamfetol were taking 1 (29/31, 94%) or 2 (2/31, 7%) prior EDS medications; patients adding solriamfetol were taking 1 (16/20, 80%), 2 (3/20, 15%) or 3 (1/20, 5%). Most patients transitioning to solriamfetol were taking wake-promoting agents (22/31, 71%); patients adding solriamfetol were most frequently taking sodium oxybate (11/20, 55%). Solriamfetol's efficacy profile was the primary reason prompting the discussion to prescribe solriamfetol de novo (12/19, 63%); need for better efficacy/augmenting effects of other medications was the primary reason for transitioning (18/31, 58%) and add-on therapy (19/20, 95%). At data collection, 63 (90%) patients were still on a stable solriamfetol dose. The most common reasons for discontinuing solriamfetol were lack of efficacy (n=3) and side effects (n=3). Conclusion: Efficacy and the need for improved efficacy over existing medication(s) were key considerations for physicians prescribing solriamfetol treatment to patients with narcolepsy in clinical practice. Support (if any): Jazz Pharmaceuticals